Human branding: From attachment strength to loyalty - Loureiro, S. M. C.; Sarmento, E. M.; Vinagre, F.; Ferreira, M. (Journal of Marketing Communications, 2025)
Human branding is everywhere and within every individual. With the increase in the importance of technology and social media, human branding becomes increasingly relevant, but it is still a branding concept with much room to explore. Celebrities, such as actors and athletes, are the greatest examples of human brands, and with social media managing public image is key to success. This study aims to analyze the process by which attachment strength influences loyalty through intimate and public engagement. Thus, a sample of 321 participants, collected through social media platforms, allowed us to treat data and test the hypotheses of the proposed model. Relatedness is the most relevant driver of attachment strength and the flow from attachment to loyalty through public engagement.